Test-retest reliability of the functional reach test and the hand grip strength test in older adults using nursing home services - Ferreira, S (2021)
This study aimed to determine the absolute and relative test-retest reliability of the functional reach test (FRT) and the handgrip strength test (HGST) in older adults using nursing homes. Methods Participants (≥ 65 years old), living in nursing homes or using their day care services, were distributed into a group without cognitive impairment (GWCI, n = 43) and a group with mild cognitive impairment (GCI; n = 22). A 1-week test-retest was performed for the FRT and the HGST. Relative reliability was measured by the intraclass correlation coefficient (ICC3.1), and absolute reliability by the standard error of measurement (SEM), minimal detectable change (MDC95), and Bland-Altman plots. Results The ICC showed high reliability for the FRT (GWCI, ICC = 0.83; GCI, ICC = 0.87) and the HGST (ICC ≥ 0.95 in both hands and participant groups). The absolute reliability was good: FRT, SEM = 2.96/2.29, MDC95 = 8.20/6.35 for the GWCI and the GCI, respectively; HGST dominant hand SEM = 1.26/0.82, MDC95 = 3.50/2.29, and HGST non-dominant hand SEM = 1.05/0.80, MDC95 = 2.90/2.21, for the GWCI and the GCI, respectively. Bland-Altman showed that there was not a systematic bias for the tests in both groups. Discussion Findings show that the FRT and the HGST are reliable, have acceptable measurement error, and may be used for research and clinical purposes to assess functional balance and strength of the hands in older adults using nursing homes.